2023
DOI: 10.1073/pnas.2217124120
|View full text |Cite
|
Sign up to set email alerts
|

Air quality equity in US climate policy

Abstract: The United States government has indicated a desire to advance environmental justice through climate policy. As fossil fuel combustion produces both conventional pollutants and greenhouse gas (GHG) emissions, climate mitigation strategies may provide an opportunity to address historical inequities in air pollution exposure. To test the impact of climate policy implementation choices on air quality equity, we develop a broad range of GHG reduction scenarios that are each consistent with the US Paris Accord targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…For example, Zhu et al evaluated two decarbonization strategies (building electrification and truck electrification) in California, and found that while building electrification generates greater overall air quality benefits (~15%), it is comparatively less beneficial to disadvantaged communities 19 . Polonik et al find potential for targeted emissions reductions to reduce disparities, based on year 2017 emissions inventories and economic activity, especially for the transportation sector; our results, based on year 2030 projections, show more limited reduction possibilities 22 . Building on this previous work, our optimization results further demonstrate that one likely reason for these insights is the tension between applying large-scale policies to air pollutants, and reducing pollution disparities for specific disadvantaged communities which are affected by different sources (as also suggested by Wang et al 30 ).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…For example, Zhu et al evaluated two decarbonization strategies (building electrification and truck electrification) in California, and found that while building electrification generates greater overall air quality benefits (~15%), it is comparatively less beneficial to disadvantaged communities 19 . Polonik et al find potential for targeted emissions reductions to reduce disparities, based on year 2017 emissions inventories and economic activity, especially for the transportation sector; our results, based on year 2030 projections, show more limited reduction possibilities 22 . Building on this previous work, our optimization results further demonstrate that one likely reason for these insights is the tension between applying large-scale policies to air pollutants, and reducing pollution disparities for specific disadvantaged communities which are affected by different sources (as also suggested by Wang et al 30 ).…”
Section: Discussioncontrasting
confidence: 49%
“…The report by Diana et al constructs a national policy scenario that reduces CO 2 emissions by 20% and air pollution damages by 50% for Black, Hispanic, and low-income populations specifically 21 . Polonik et al recently examined a range of U.S. GHG reduction scenarios, finding that least-cost and income based reductions can exacerbate air pollution disparities for racial/ethnic minorities, and that reducing transportation emissions has the most potential to reduce racial inequities 22 .…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that EV penetration would be associated with changes in delivery, resulting in potentially higher mileage to accommodate charging. Besides, disparities in exposure cannot be completely resolved by relying only on electrification, ,, initiatives that reduce truck mileage in disadvantaged neighborhoods should be pursued. In this study, the assumptions for the non-exhaust emissions of electric trucks used in the CTM model are subject to substantial uncertainty due to the limited number of studies on the non-exhaust emissions of electric trucks resulting in generalizable emission factors.…”
Section: Discussionmentioning
confidence: 99%
“…41 of 1999, then the air quality is suitable for human habitation. Air quality levels will be highest close to the source and gradually decline as distance increases [15]. As a result of their ability to cause pollutants to move from one location to another, wind direction and speed are crucial factors in the spread of pollutants.…”
Section: Introductionmentioning
confidence: 99%